Corporate Social Responsibility, Good Corporate Governance, and Banking Financial Performance : Empirical Evidence from Panel Data Analysis of Banks in Indonesia: Corporate Social Responsibility, Good Corporate Governance, dan Kinerja Keuangan Perbankan : Bukti Empiris dari Analisis Data Panel Bank di Indonesia - Almaraja Ihuton Limbong (Jurnal Bisnis dan Ekonomi, 2026)
Objective : CSR was measured using the Corporate Social Responsibility Disclosure Index (CSRDI) based on the Global Reporting Initiative (GRI Standards), while GCG was proxied by board of commissioners size and audit committee size. Financial performance was measured using Return on Assets (ROA). Methodology : This study employed a quantitative research approach with a sample of 11 banking companies selected through purposive sampling, resulting in 55 firm-year observations. The data were analyzed using panel data regression, with the Common Effect Model (CEM) identified as the most appropriate model based on the model selection tests. Research Results :  The findings indicate that CSRDI and audit committee size have a positive and statistically significant effect on ROA, whereas board of commissioners size has no significant effect. Furthermore, CSRDI, board of commissioners size, and audit committee size jointly have a significant effect on ROA. These findings underscore the importance of CSR disclosure and the effectiveness of the audit committee in enhancing the financial performance of banking companies.